2014
DOI: 10.2217/rme.14.30
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy for the Treatment of Amyotrophic Lateral Sclerosis: Signals for Hope?

Abstract: Based on the distinctive cellular, molecular and immunomodulatory traits of mesenchymal stem cells (MSC), it has been postulated that these cells may play a critical role in regenerative medicine. In addition to the participation of MSC in the repair of mesodermal-derived tissues (bone, cartilage), robust data have suggested that MSC may also play a reparative role in conditions involving damage of cells of ectodermal origin. The above content has been supported by the capability of MSC to differentiate into n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…The identification that OM-MSCs secrete higher levels of the chemokine CXCL12 than BM-MSCs (Lindsay et al., 2016), which we and others have shown to be important in augmenting endogenous myelination (Maysami et al., 2006, Lindsay et al., 2013, Lindsay et al, 2016 Zilkha-Falb et al., 2016) also adds to the desirability as a candidate cell for transplantation. Lastly as MSCs are known to home to damaged tissue (Laroni et al., 2013, Eseonu and De Bari, 2015) and secrete a plethora of pro-repair factors, their use as a treatment is more beneficial than application of a chemokine alone (Allers et al., 2014, Joyce et al., 2010, Laroni et al., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The identification that OM-MSCs secrete higher levels of the chemokine CXCL12 than BM-MSCs (Lindsay et al., 2016), which we and others have shown to be important in augmenting endogenous myelination (Maysami et al., 2006, Lindsay et al., 2013, Lindsay et al, 2016 Zilkha-Falb et al., 2016) also adds to the desirability as a candidate cell for transplantation. Lastly as MSCs are known to home to damaged tissue (Laroni et al., 2013, Eseonu and De Bari, 2015) and secrete a plethora of pro-repair factors, their use as a treatment is more beneficial than application of a chemokine alone (Allers et al., 2014, Joyce et al., 2010, Laroni et al., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Minguell et al (2013) showed that after 18 months of intrathecal injection of bone marrow-derived MSC, patients became significantly stable with an appreciably improved quality of life.…”
Section: Types Of Stem Cells Utilized In Cell Therapymentioning
confidence: 99%
“…(44) The recent success in culturing a whole optic disc in-vitro which has a large number of photoreceptors might be generated from embryonic stem cells without the need for embryo donor; this can be transplanted to restore the photosensitive component and hence vision in blind patients. (45) In-vitro trials for general neurological disorders Blood brain barrier (BBB) is a major determinant in neuroregeneration. After inflammation, BBB shows increased permeability allowing inflammatory cell leakage, thus exaggerating injury.…”
Section: In-vitro Trials Involving Mechanisms Of Stem Cell-mentioning
confidence: 99%